Impact of UV-C Stimulation of Tubers, Immersion of Potato Sticks in Water and Frying Fat Type on the Content of Fat in Dry Mass of French Fries (Agricultural Engineering, 2020)
The aim of the experiment was to determine the impact of UV-C stimulation of tubers, immersion of potato sticks in water, and a frying fat type on the content of fat in dry mass of French fries. Tests were carried out on Innovator tubers which is one of the most often used cultivator in production of French fries by the European and Polish companies. Radiation of potato tubers with ultraviolet in band C were performed with the use of the original stand for stimulation of biological material with electro-magnetic radiation. A statistical analysis of the obtained results of tests indicates that stimulation of tubers and a type of frying fat had a statistically significant impact on the fat content in dry mass of French fries.